Students perception of moral education textbooks design components and learnability - Mohd Mokhtar, Mohamed Hilmie; Yasin, Maizura (Canadian Center of Science and Education, 2021)
Textbooks are one of the most fundamental learning and teaching tools used in schools all around the world (Nicholls, 2003). Today's technology allows students to access a variety of textbook formats, including online textbooks that they may read from anywhere. This study looks into the style and arrangement of learning textbooks in Malaysia in order to make studying more convenient. The purpose of this research is to see if the dynamics of textbook layout affect students' desire to learn. Thirty Year 6 children from a primary school in the Selangor district of Hulu Langat participated in this study. Students' views of textbook design elements, such as paper quality, printing, colour, and pedagogical aspects, were determined using a quantitative survey. Print and colour were scored higher by the students than paper quality, artwork, and images, according to the data. Furthermore, the research discovered a link between the layout of a book and its actual use.